Exploring transformative learning in vocational online and distance education - Mark Nichols; Neeru Choudhary; Doug Standring (Flexible Learning Association of New Zealand, 2020)
reformulation of their experience, and new ways of acting in the world) is widely understood as an important outcome of adult education (Mezirow, 1990, 2018). Various studies have been performed over the last 30 or so years since Mezirow's theory was first proposed, confirming its presence and importance in higher education. However, it is questioned as to whether transformative learning takes place in vocational distance and online education, particularly if not explicitly promoted.   This paper investigates the extent of transformative learning taking place in adult learners studying at a distance, online. Drawing on King's (2009) Learning Activities Survey (LAS), Open Polytechnic students (n=499) across 7 qualifications (6 discipline areas) responded to a survey asking about their experiences of perspective transformation. The instrument also sought insight as to how vocational providers of vocational online and distance education might promote transformative learning outcomes in learners. Survey results show evidence of perspective transformation in students, to varying degrees mainly determined by the qualification being studied. The results also reveal which instructional design approaches and teaching activities might contribute to transformation.